Effect of high speed dry end milling on surface roughness and cutting forces of Ti-6Al-4V ELI - Sharif, S.; Safari, H.; Izman, S.; Kurniawan, Denni (2014)
The surface quality generated when high speed dry end milling (HSDEM) Ti-6Al-4VELI titanium alloy with coated and uncoated carbide tools were investigated. Evaluation was conducted using TiAlN+TiN coated and uncoated cemented carbide tools under different high cutting speeds and feed rates conditions. Surface roughness and cutting forces were measured when using new tools. The milled surface quality and corresponding alteration were characterized through electron microscopy. Within the investigated conditions high quality surface finish was obtained on the machined surface. Increasing cutting speed from 200 to 300 m/min during the process improved the surface finished particularly under lower feed rates. In term of generated surface quality, uncoated H25 grade carbide tools out performed coated F40M grade specifically at the higher cutting conditions. The main damages observed after HSDEM on the surface for all machining conditions contain redeposited materials, feed marks, and tool edge marks. Under both tested feed rates the resultant cutting force decreased by increasing the cutting speeds and uncoated carbide tools provide the lower cutting forces compared to coated types. © (2014) Trans Tech Publications, Switzerland.